Role of personalization in shaping attitudes towards social media ads - Aydın, Gökhan (IGI Global, 2021)
The present article aims to understand attitudes towards social media ads, one of the most recent and rapidly growing forms of digital advertisements. So far, little attention has been paid in developing countries to the most rapidly growing type of advertising and the present study aims to contribute to fill this research gap. A survey study was carried out to understand the attitudes using Ducoffe's advertising value model and extending it by the inclusion of "rewards" and "personalization" constructs. Facebook ads are used as a proxy for social media ads and a total of 327 questionnaires were collected from Turkish consumers, which were filtered down to 281 and analyzed using structural equation modelling. The findings indicate that credibility, personalization, informativeness and entertainment have direct positive effects on advertising value and have indirect effects on attitudes towards social media ads. Personalization emerged as a significant factor affecting all other related constructs.
Keywords: Social Media; Role of Personalization; Attitudes